2022
DOI: 10.1126/sciadv.abo0514
|View full text |Cite
|
Sign up to set email alerts
|

CAR density influences antitumoral efficacy of BCMA CAR T cells and correlates with clinical outcome

Abstract: Identification of new markers associated with long-term efficacy in patients treated with CAR T cells is a current medical need, particularly in diseases such as multiple myeloma. In this study, we address the impact of CAR density on the functionality of BCMA CAR T cells. Functional and transcriptional studies demonstrate that CAR T cells with high expression of the CAR construct show an increased tonic signaling with up-regulation of exhaustion markers and increased in vitro cytotoxicity but a decrease in in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 68 publications
(111 reference statements)
1
32
0
Order By: Relevance
“…In line with this, our data show that regulating CAR signaling strength with CCT fusion prevents CAR-T cells from excessive stimulation and enables durable response against tumor cells. CAR signaling needs to be tightly regulated to achieve the fine-tuned balance of sufficient signaling for effective tumor antigen detection and CAR-T action, while also circumventing the detrimental effects seen in CARs with an excessively high affinity or expression 8, 50, 51 . This resonates in our results with CAR-3CCT cells, as these cells exhibited the best killing capability under repeated stimulation in vitro yet performed worse than the control CAR-T cells in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, our data show that regulating CAR signaling strength with CCT fusion prevents CAR-T cells from excessive stimulation and enables durable response against tumor cells. CAR signaling needs to be tightly regulated to achieve the fine-tuned balance of sufficient signaling for effective tumor antigen detection and CAR-T action, while also circumventing the detrimental effects seen in CARs with an excessively high affinity or expression 8, 50, 51 . This resonates in our results with CAR-3CCT cells, as these cells exhibited the best killing capability under repeated stimulation in vitro yet performed worse than the control CAR-T cells in vivo .…”
Section: Discussionmentioning
confidence: 99%
“… 58 , 59 Previous studies demonstrate that CAR functionality is regulated by the density of target antigen, and low antigen expression contributes to the limitation of antitumor efficacy of CAR-T cells. 60 , 61 Our in vitro studies addressed the safety issue in using human normal tissue array chips and examined the cell killing ability within anti-HLA-G CAR-T cell therapy in primary cell cultures. Our animal study has also demonstrated that there was no adverse reaction during anti-HLA-G CAR-T cell treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Translational research suggests that CAR density and antigen binding affinity influence the functionality of BCMA CAR-T cells in unexpected ways. While one might suspect that more CARs per individual T cell would correspond to more cancer cell death, higher CAR expression may actually be associated with increased T-cell exhaustion and decreased CAR-T cell infiltration into the bone marrow ( 16 ). In the future, modifications to viral promoter genes or CRISPR-mediated precision regarding the location of CAR insertion into the host genome may allow for manipulation of expected levels of CAR expression per cell ( 17 – 19 ).…”
Section: Stronger Engines: More Potent Antigen Targetingmentioning
confidence: 99%